First feeding of walking catfish (Clarias macrocephalus) - Husain, A. K. M. Akhter; Lin, Chang Kwei; Wee, Kok Leong; Little, David C.; British Council (Bangkok : Asian Institute of Technology, 1988)
Five experiments were conducted to elucidate the first feeding of walking catfish( Clarias macrocepha lus). Moina macrocopa feeding on heterotrophs and autotrophs were ana lysed separately, their proximat e composition was 70% protein ,12% crude fat,5% ash, and its wet biomass contained 90% moisture. Fry feeding rate was determined on five Mo i na densities (10, 25, 50, 100 and 150 Moina) per fry of different ages ( 5, 10 and 15 days), their gastric evacuat ion rate was determined at time intervals of 10, 30, 60 and 120 minutes. The feeding rate of 5-, 10- and 15-day old fry was 12.4, 12.2 and 40.7 Moina /fry/feeding , respectively. Feeding r ate and gastric evacuation rate increased with increasing f ry age. Rea ring of Clarias fry wi th different diets (live Moina, frozen Moina, dried Moina , beef liver plus fish flesh and Powder feed indicates that it is impractical to r ear Clarias fry with avail able artificial diets as first feed because of low survival . Fry survival with l ive Moina feed was 79%, frozen Moina 40%, powder feed 17% and the dried Moina and Beef liver were 0% during a 15 -day rearing period. Survival and growth rates were determined for Clarias fry fed on live Moina for different time periods (5, 8 and 10 days) and then reared the same fry with four experimental diets for 15,12 and 10 days, r espectively. Average fry daily feeding rate was live Moina 34% and 30% artificial diets (dry wt.basis) of body weight. Fry fed with live Moina produced maximum survival rate , growth rate and feed conversion ratio among all the diets tested. Clarias fry were reared at 5 different densities (10, 25 , 50, 100 and 250 fry/L) in recirculated wate r system show that fry growth rate and survival were not significant ly different among various stocking density.
A Thesis submitted in partial fulfilment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Fish-culture; Catfishes